A, Analisis Analisis Konstruksi Sosial Citra Program Studi Ilmu Komunikasi Pada Mahasiswa Dalam Memilih Studi di Universitas Islam Syekh Yusuf: Konstruksi sosial citra - Aqmarina, Disha; Putri R, Jeany; Andriani, Yudithia; Qolbiyah , Najmi (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
This research provides an in-depth understanding of how the image of a university is formed among new students at Syekh Yusuf Islamic University. Using a qualitative approach and interview techniques, the study allows for insights into the perspectives and direct experiences of new students. The findings indicate that the positive image of Syekh Yusuf Islamic University among new students is reflected in aspects such as quality teaching staff, relatively affordable tuition fees, strategic location, and the success of alumni in the workforce. This suggests that these aspects play a significant role in shaping the positive image of a university. Furthermore, the research also illustrates how the social construction of a positive image of Syekh Yusuf Islamic University is formed. These processes allow new students to form their views of the university based on their interactions with social media, family, community, and school. This indicates that the image of a university is not only influenced by direct experiences on campus but also by the influence of a broader social environment. Thus, this research makes an important contribution to understanding how the image of a university is formed and influenced by social factors, as well as its implications for the perceptions and choices of new students in selecting their university.